Punitive society, death and war: a rereading from Michel Foucault - Souza, Luís Antônio Francisco de; Barros, Rodolfo Arruda Leite de (FCL-UNESP Laboratório Editorial, 2015)
Within a broad debate on the crisis of modernity, emerges a concern about the loss of references and return of violence as a constitutive part of contemporary politics. Garland (2008) and Wacquant (2001) show that there is a crisis in the foundations of contemporary penal systems, but these changes occur at the same time as the expansion of crime-control mechanisms that led to the hardening of the penal law and the dissemination of social control strategies. From these findings on recent transformations in contemporary criminal justice system and the return of violence as a constitutive mechanism of politics, this paper investigates the extent to which these recent trends in criminal practices run counterwise to the trend towards the militarization of security. Alongside these reflections, this paper investigates, with the contributions of Foucault, how these punitive mechanisms could not symbolize a (re) approximation of punitive forms of modernity toward a biopolitics, or even, a tanatospolitics (AGAMBEN, 2004a). Do punitive strategies find their anchorage in war? In this sense, militarism, as the essence of exception, potentiates the unpunished death? The conclusion points to the establishment of public security policies as a death device as well.could not symbolize a (re) approximation of punitive forms of modernity toward acould not symbolize a (re) approximation of punitive forms of modernity toward a biopolitics, or even, a tanatospolitics (AGAMBEN, 2004a). Do punitive strategies find their anchorage in war? In this sense, militarism, as the essence of exception, potentiates the unpunished death? The conclusion points to the establishment of public security policies as a death device as well.could not symbolize a (re) approximation of punitive forms of modernity toward a biopolitics, or even, a tanatospolitics (AGAMBEN, 2004a). Do punitive strategies find their anchorage in war? In this sense, militarism, as the essence of exception, potentiates the unpunished death? The conclusion points to the establishment of public security policies as a death device as well.biopolitics, or even, a tanatospolitics (AGAMBEN, 2004a). Do punitive strategiesfind their anchorage in war? In this sense, militarism, as the essence of exception,potentiates the unpunished death? The conclusion points to the establishment ofpublic security policies as a death device as well.